2022
DOI: 10.3390/cells11182775
|View full text |Cite
|
Sign up to set email alerts
|

Proteome and Glycoproteome Analyses Reveal the Protein N-Linked Glycosylation Specificity of STT3A and STT3B

Abstract: STT3A and STT3B are the main catalytic subunits of the oligosaccharyltransferase complex (OST-A and OST-B in mammalian cells), which primarily mediate cotranslational and post-translocational N-linked glycosylation, respectively. To determine the specificity of STT3A and STT3B, we performed proteomic and glycoproteomic analyses in the gene knock-out (KO) and wild-type HEK293 cells. In total, 3961 proteins, 4265 unique N-linked intact glycopeptides and 629 glycosites representing 349 glycoproteins were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…According to the report by Wen et al [47] , although there were different preferences for glycosylation sites between the OST-A complex and the OST-B complex, in the absence of one of them, the other complex can act as a compensatory role to complement the intracellular glycosylation process, which may explain why the silencing of STT3B did not cause lethal ER stress.…”
Section: Discussionmentioning
confidence: 98%
“…According to the report by Wen et al [47] , although there were different preferences for glycosylation sites between the OST-A complex and the OST-B complex, in the absence of one of them, the other complex can act as a compensatory role to complement the intracellular glycosylation process, which may explain why the silencing of STT3B did not cause lethal ER stress.…”
Section: Discussionmentioning
confidence: 98%
“…Aberrant glycosylation is ever-present in oncogenic transformation, with a capital influence on tumor progression, immune evasion, invasiveness, metastatic potential, and (radio)­chemoresistance. Consequently, numerous studies have addressed the importance of glycosylation in several types of cancer, including CRC. , However, the impact of aberrant glycosylation is complex because it encompasses the glycosylation pattern and the proteome composition, not exclusively the glycoenzymes . Furthermore, changes in the glycosylation machinery affect the biological activity and interactome of glycoproteins, magnifying the map of alterations due to impaired glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“… 42 , 43 However, the impact of aberrant glycosylation is complex because it encompasses the glycosylation pattern and the proteome composition, not exclusively the glycoenzymes. 44 Furthermore, changes in the glycosylation machinery affect the biological activity and interactome of glycoproteins, magnifying the map of alterations due to impaired glycosylation. This critical consideration has not always been addressed with the degree of attention it deserves, 45 , 46 so our study has leveraged the multiomic proteomic and glycomic approach to assess more closely the extent of glycosylation changes in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…46 Current studies have shown that the OST complex is involved in the maintenance of the ER homeostasis, and the loss or abnormal function of its composition affects the ER stress state in cells. 15 Wen et al 47 found that the lack of STT3A in human embryonic kidney cells HEK293 caused ER stress and activated the UPR pathway, and Ding et al 48 found that the loss of RPN1, a non-catalytic subunit of the OST complex, caused ER stress-mediated apoptosis in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%